‘A process where we’re all at the table’: community archives challenging dominant modes of archival practice - Zavala , Jimmy; Migoni , Alda Allina; Caswell , Michelle; Geraci , Noah; Cifor , Marika (Archives & Manuscripts, 2017)
Community archives have compelled shifts in dominant archival management practices to reflect community agency and values. To analyse these shifts, we ask: In what ways do community archives and their staff challenge traditional archival modes of practice? Do community archives work within or against dominant frameworks for institutional sustainability? Do community archives challenge or replicate dominant custody practices? Based on semi-structured interviews with 17 founders, staff and volunteers at 12 Southern California community archives, this research examines the diverse models of practice utilised by community archives practitioners that diverge from and challenge standard practices in the field. By addressing these questions, our research uncovers a variety of models of practice employed by communities in Southern California to autonomously create and sustain their archives.